2020
DOI: 10.2147/jmdh.s285668
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of Care in a Nursing Home as Experienced by Patients with Dementia</p>

Abstract: Background Dementia care is one of the most rapidly growing areas in health care. Despite this, relatively little is known about the experiences of persons with dementia in relation to quality of care. Objective The aim of this study was to describe how persons with dementia in nursing homes experience the quality of care. Design A cross-sectional design was used. Setting and Participants The study was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…No quantitative instruments for measuring and evaluating the quality of care in the hospital setting were identified in the published research, despite the obvious appeal of standardised instruments in evaluating health outcomes in the fast‐paced hospital environment. Initial scoping for this study identified two quality of care questionnaire instruments for use in the aged care setting (Helgesen et al, 2020; Ratcliffe et al, 2019), but nothing specifically designed for acute care. Future research could investigate the viability of such tools in the hospital setting, as these would be useful in assessing the impact of interventions targeted at improving the care experiences of this vulnerable cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No quantitative instruments for measuring and evaluating the quality of care in the hospital setting were identified in the published research, despite the obvious appeal of standardised instruments in evaluating health outcomes in the fast‐paced hospital environment. Initial scoping for this study identified two quality of care questionnaire instruments for use in the aged care setting (Helgesen et al, 2020; Ratcliffe et al, 2019), but nothing specifically designed for acute care. Future research could investigate the viability of such tools in the hospital setting, as these would be useful in assessing the impact of interventions targeted at improving the care experiences of this vulnerable cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Standardised dementia‐specific instruments for assessing quality of care in the hospital setting would enable health care providers to regularly evaluate and improve services, but such questionnaires may be challenging for people with severe cognitive, functional, and/or sensory impairments (Goldberg & Harwood, 2013; Ratcliffe et al, 2019; Van Baalen et al, 2011). Two quality‐of‐care instruments have been recently developed for use in the aged care setting (Helgesen et al, 2020; Ratcliffe et al, 2019), but preliminary literature searches reveal a lack of such validated instruments suited to the acute hospital care setting. Moreover, while Digby et al's (2016) discursive article outlines some of the challenges their research team experienced when collecting qualitative data from people with dementia—and the strategies they used to overcome these—detailed practical guidance on how to effectively collect this type of data is largely lacking from clinical practice guidelines and the extant academic literature.…”
mentioning
confidence: 99%
“…Our findings are in line with previous results indicating positive outcomes from educating patients and nurses with improvement in their knowledge about delirium. 27 , 28 It is important to expand this approach of educating patients and caregivers nationwide, for earlier identification, prevention, and better management of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim is to share our experiences and lessons learned when applying the A-PM in a nursing home (NH) setting for a project designed to gain insight into the experiences of residents. The resident experience of quality of care has primarily been studied with interview-based approaches (Coughlan & Ward, 2007; Helgesen et al, 2020), which can lack authentic insight into the resident experience and reduce the residents’ role in NH to care recipients. The A-PM has a unique ability to change the focus on residents from self-contained care recipients to agents making goal-oriented actions within interpersonal processes.…”
Section: Introductionmentioning
confidence: 99%